Optimization analysis of solid oxide fuel cells with ceria-based single cells using computational fluid dynamics - Tan, Kang Huai; Mohd Azami, Mohammad Saifulddin; Abd. Rahman, Hamimah; Abd Rahman, Nurul Farhana; Tukimon, Mohd Faizal; Jaidi, Zol Hafizi; Yusop, Umira Asyikin (2023)
The SOFC simulations in this research are conducted at temperatures of 600°C, 700°C, and 800°C, focusing on the Ni-SDC anode, SDC electrolyte, and LSCF-SDC materials used in the SOFC single cell. Initially, the single-cell model is created using CAD software, followed by the development of a computational fluid dynamics (CFD) model with the requisite material properties. The study then proceeds to simulate temperature distribution and cell performance for various supported SOFC stack models (electrode and electrolyte supported) at intermediate temperatures. Subsequently, the study examines cell performance with varying thicknesses of the anode, electrolyte, and cathode components within the specific supported single cell. In summary, the CFD results indicate that cathode-supported SOFCs exhibit higher power density, specifically 938.28 mW/cm2 at 800°C, surpassing anode-supported and electrolyte-supported configurations. The power density reaches 1495.40 mW/cm2 when the single-cell layer thickness is 0.35 mm for the cathode, 0.02 mm for the anode, and 0.01 mm for the electrolyte. However, electrolyte-supported single cells display the lowest temperature difference, at 0.028% at 800oC The simulation results demonstrate that reducing the thicknesses of all electrodes and the electrolyte leads to increased current density, power density, and temperature distribution difference